Writing home : walking, literature and belonging in Australia's Red Centre - Morrison, Glenn Andrew (Melbourne University Publishing, 2017)
Writing Home explores the literary representation of Australian places by those who have walked them. In particular, it examines how Aboriginal and settler narratives of walking have shaped portrayals of Australia's Red Centre and consequently ideas of nation and belonging. Central Australia has long been characterised as a frontier, the supposed divide between black and white, ancient and modern. But persistently representing it in this way is preventing Australians from re-imagining this internationally significant region as home. Writing Home argues that the frontier no longer adequately describes Central Australia, and that the Aboriginal songlines make a significant but under-acknowledged contribution to Australian discourses of hybridity, belonging and home. Drawing on anthropology, cultural theory, journalism, politics and philosophy, the book traces shifting perceptions of Australian place and space since precolonial times, through six recounted walking journeys of the Red Centre.